2017
DOI: 10.1016/j.jogn.2016.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Review of Technology to Support Communication With Parents of Infants in the NICU

Abstract: Objective-To synthesize findings from the published literature on the use of technology in the NICU to improve communications and interactions among health care providers, parents, and infants.Data Sources-Electronic databases including Ovid MEDLINE, CINAHL, Web of Science, and Google Scholar were searched for related research published through May 2016. The reference lists of all studies were reviewed, and a hand search of key journals was also conducted to locate eligible studies.Study Selection-Eleven studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 37 publications
2
39
0
2
Order By: Relevance
“…10,11 Video calls or livestreaming video of premature newborns has also been described for family support during long NICU hospitalizations. 12 With many health care facilities limiting in-patient visitation in response to the COVID-19 pandemic, telemedicine could be used to support families who cannot visit due to exposure concerns. Formal evaluations of family satisfaction with inpatient services provided via telemedicine, and the degree to which this supports patient and family-centered care are needed.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Video calls or livestreaming video of premature newborns has also been described for family support during long NICU hospitalizations. 12 With many health care facilities limiting in-patient visitation in response to the COVID-19 pandemic, telemedicine could be used to support families who cannot visit due to exposure concerns. Formal evaluations of family satisfaction with inpatient services provided via telemedicine, and the degree to which this supports patient and family-centered care are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, when visitation is limited or restricted, building that trust may be difficult. Alternative methods of communication which include a video component have been studied [ 18 ].…”
Section: Solutions For Supporting Familiesmentioning
confidence: 99%
“…The referral NICU can promote bonding by forming connections between parents and newborns through communication (cameras, iPads, and smartphone applications), 27,28 sound (voice or heartbeat), [11][12][13] and scent (swapped scented cloths). Since most of our mothers have their own smart phones, we have found that it is easier for them to receive videos or recordings of their newborn.…”
Section: Discussionmentioning
confidence: 99%